NATO Nuclear Burden-Sharing Post -Crimea: What Constitutes "Free-Riding"? - Bell, Robert. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2021.; Submitted to the Dept. of Diplomacy, History, and Politics.; Advisor: Robert Pfaltzgraff.; Committee: Richard Shultz, and Nicholas Burns.; Keywords: International relations, Military studies, and European studies.